Antibiotics and antibiotic resistance genes in anaerobic digesters and predicted concentrations in agroecosystems. (1st January 2022) - Visca, Andrea; Rauseo, Jasmin; Spataro, Francesca; Patrolecco, Luisa; Grenni, Paola; Massini, Giulia; Mazzurco Miritana, Valentina; Barra Caracciolo, Anna
Abstract: In recent decades, the innovative practice of management and valorization of agrozootechnical waste as energy through anaerobic digestion (AD) has been rapidly growing. However, whether applying digestate to soil as biofertilizer can be a source of antibiotics (ABs) and antibiotic resistance genes (ARGs) has not been fully investigated so far. In this work the ARGs responsible for sulfamethoxazole (SMX) resistance ( sul1, sul2 ), ciprofloxacin (CIP) resistance ( qnrS, qepA, aac-(6′)-Ib-cr ) and the mobile genetic element intl1, together with the concentrations of the antibiotics SMX and CIP, were measured in several anaerobic digesters located in Central Italy. Based on these results, the concentrations of antibiotics and ARGs which can potentially reach soil through amendment with digestate were also estimated. The highest CIP and SMX concentrations were found during winter and spring in anaerobic digesters. The highest ARG abundances were found for the aac-(6')-Ib-cr and sul2 genes. The overall results showed that application of digestate to soil does not exclude AB contamination and spread of ARGs in agroecosystems, especially in the case of ciprofloxacin, owing to its high intrinsic persistence. Highlights: Antibiotics and resistance genes were evaluated in seasonal samplings in anaerobic digesters. The highest SMX and CIP concentrations were found during spring and winter. The highest abundances of ARGs were found during winter season. Both CIP and its ARGs were generally more abundant than SMX over the year.